PENGARUH AUDIT TENURE, UKURAN KAP DAN FEE AUDIT TERHADAP INTEGRITAS LAPORAN KEUANGAN - Yulianti, Maissy Syahri; Novianti, Neva; Puspa, Dwi Fitri (Jurnal Kajian Akuntansi dan Auditing, 2025)
This study aims to empirically prove the influence of audit tenure, public accounting firm (KAP) size and audit fees on the integrity of financial statements. In this study, the sampling method uses purposive sampling, which resulted in 27 infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) in the 2021-2023 period with a total of 81 data, used as populations and samples. This study uses secondary data, namely annual reports and company financial statements obtained from www.idx.co.id websites and company websites. The data analysis methods applied include descriptive statistical analysis and multiple linear regression analysis of panel data with the help of eviews 12 software. The results of this study show that the audit tenure variable and the size of KAP have an effect on the integrity of financial statements, and the audit fee variable has no effect on the integrity of financial statements.